Social Identity Construction in Digital Communities: A Case Study on Social Media Users in Indonesia - Han Gyeol Yang; Thalita Syifa Fatimah (International Journal of Psychology and Health Science, 2023)
This study aims to explore the process of social identity construction within digital communities in Indonesia using the Social Identity Theory approach. With a qualitative case study design, data were collected through in-depth interviews, participant observation, and content analysis from various digital communities such as fandoms, social activism groups, and hobby groups. The findings indicate that social media plays a crucial role in facilitating the formation of social identity through social categorization, social identification, and social comparison processes. Social media provides a dynamic space for individuals to find groups with similar interests, internalize community norms, and reinforce solidarity through symbols and collective activities. The collectivist culture of Indonesia influences social identity formation, reflected in the integration of local values such as the use of regional languages and cultural symbols in online interactions. However, challenges like polarization, cyberbullying, and social pressure also emerge, hindering the dynamics of digital communities. These findings affirm that social media is not only a communication tool but also a complex space that facilitates social identity formation with intertwined opportunities and risks. The results contribute theoretically to social psychology and digital culture literature and provide practical insights for managing inclusive and harmonious digital communities.